Digital technology and economic impacts of COVID-19: Experiences of the People's Republic of China - Yiping Huang; Han Qiu; Jing Yi Wang (Asian Development Bank Institute (ADBI), 2021)
Digital technology has rapidly transformed the PRC's economy over the past decade, especially in areas of e-commerce and digital finance. In many ways, digital technology changes the pattern of economic operation, as it enlarges business scale, increases economic efficiency, improves user experiences, reduces operating costs, and controls financial risks. Digital technology served as an important economic stabilizer during COVID-19, by accurately tracking down confirmed infected cases, moving a lot of economic activities online and issuing consumption coupons by local governments. These not only enabled the PRC to be the first to come out of the pandemic and to achieve impressive V-shaped recovery, but also with 5G and other technological and infrastructural development, the digital economy in the PRC will likely grow more rapidly in the coming years, bringing about more fundamental changes. However, the authorities will also need to address a wide range of policy issues to ensure the smooth development of the digital economy, including the easing of the data inequality problem, protection of individual rights, and regulation of platform behavior.
Keywords: G23; E60; O31; 330; digital technology; digital economy; COVID-19; PRC